Peningkatan Pemasaran Produk pada Kelompok Wanita Tani Sri Rejeki di Desa Cabeyan Sukoharjo - Nugraheni, Ambar Yunita; Purbasari, Heppy; Utami, Wahyu; Cholisoh, Zakky; Nurwaini, Setyo; Kusumowati, Ika Trisharyanti Dian; Wikantyasning, Erindyah Retno; Munawaroh, Rima; Hanwar, Dedi; Larasati, Arindra; Ramdani, Tasya Eka (Abdi Geomedisains, 2025)
Kelompok Wanita Tani (KWT) Sri Rejeki in Cabeyan Village, Sukoharjo, is a community of women actively engaged in plant cultivation and the production of instant herbal products such as ginger and temulawak (curcuma). However, their product marketing activities are still limited to conventional methods and have not yet reached digital marketing platforms. This community service activity aimed to enhance the knowledge and skills of KWT members in digital product marketing through educational sessions and practical training. The methods used included interactive lectures, group discussions, and hands-on practice related to the use of social media and e-commerce platforms. The educational materials covered product marketing and basic understanding of Break Even Point (BEP) calculation. A total of 18 active KWT members and 5 teenagers participated in this activity. The participants' knowledge test results before (pre-test) and after (post-test) the educational session showed an increase in the average knowledge level, from the fair category (63.77%) to the good category (97.10%). KWT members began to understand the importance of market segmentation, slogan development, and the use of digital platforms such as WhatsApp Business, Instagram, and Shopee. This activity demonstrated that participatory training could equip participants with practical skills to improve their product marketing strategies. It is recommended that an internal marketing team be formed and continuous mentoring provided to optimize digital marketing efforts and product legality aspects such as PIRT (Home Industry Food Permit) and halal certification.